Hikmah Penetapan Ibadah Perspektif Teologi dan Fikih Islam: The Wisdom of Worship in Islamic Theology and Jurisprudence - M. Fadli; Lomba Sultan; Rahmatiah HL (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study examines the wisdom behind the establishment of worship in Islam through an interdisciplinary approach combining Islamic theology and jurisprudence, positioning worship not merely as ritual performance but as a multidimensional system enriched with rational, spiritual, and social values. The purpose of this research is to uncover the theological foundation of worship as an embodiment of monotheism and to analyze the jurisprudential framework that regulates worship through divinely mandated pillars, conditions, and procedures. Employing a qualitative-descriptive methodology, the study conducts textual analysis of the Qur’an, the Sunnah, and classical works such as those of al-Ghazālī, al-Nawawī, and Ibn Taymiyyah, along with contemporary scholarship including Wahbah al-Zuḥaylī, Yūsuf al-Qaraḍāwī, and Ṭāhir ibn ‘Āsyūr. The findings reveal that worship serves dual functions: as a spiritual purification process fostering divine consciousness, and as a system of public welfare promoting justice, solidarity, and moral formation within society. This research contributes to the discourse of Islamic theology and jurisprudence by integrating maqāṣid al-sharī‘ah as an analytical framework, enabling worship to be understood not merely as a legal obligation but as a transformative structure capable of shaping both inner spirituality and social ethics in contemporary life.